Identifying prey capture events of a free-ranging marine predator using bio-logger data and deep learning - Schoombie, Stefan; Jeantet, Lorène; Chimienti, Marianna; Sutton, Grace J.; Pistorius, Pierre A.; Dufourq, Emmanuel; Lowther, Andrew D.; Oosthuizen, W. Chris (Royal Society Open Science, 2024)
Marine predators are integral to the functioning of marine ecosystems, and their consumption requirements should be integrated into ecosystem-based management policies. However, estimating prey consumption in diving marine predators requires innovative methods as predator-prey interactions are rarely observable. We developed a novel method, validated by animal-borne video, that uses tri-axial acceleration and depth data to quantify prey capture rates in chinstrap penguins (Pygoscelis antarctica). These penguins are important consumers of Antarctic krill (Euphausia superba), a commercially harvested crustacean central to the Southern Ocean food web. We collected a large data set (n = 41 individuals) comprising overlapping video, accelerometer and depth data from foraging penguins. Prey captures were manually identified in videos, and those observations were used in supervised training of two deep learning neural networks (convolutional neural network (CNN) and V-Net). Although the CNN and V-Net architectures and input data pipelines differed, both trained models were able to predict prey captures from new acceleration and depth data (linear regression slope of predictions against video-observed prey captures = 1.13; R2 approximate to 0.86). Our results illustrate that deep learning algorithms offer a means to process the large quantities of data generated by contemporary bio-logging sensors to robustly estimate prey capture events in diving marine predators.
Publisher: Royal Society
Keywords: Sørishavet; biologging; krill; marin biologi; marin zoologi; marine økosystemer; pingviner; plankton

Large-scale seabird community structure along oceanographic gradients in the Scotia Sea and northern Antarctic Peninsula - Ollus, Victoria Marja Sofia; Biuw, Martin; Lowther, Andrew; Fauchald, Per; Deehr Johannessen, John Elling; Martín López, Lucía Martina; Gkikopoulou, Kalliopi C.; Oosthuizen, W. Chris; Lindstrøm, Ulf (Frontiers in Marine Science, 2023)
Introduction: The Scotia Sea and Antarctic Peninsula are warming rapidly and changes in species distribution are expected. In predicting habitat shifts and considering appropriate management strategies for marine predators, a community-level understanding of how these predators are distributed is desirable. Acquiring such data, particularly in remote areas, is often problematic given the cost associated with the operation of research vessels. Here we use cruise vessels as sampling platforms to explore seabird distribution relative to habitat characteristics. Methods: Data on seabird at-sea distribution were collected using strip-transect counts throughout the Antarctic Peninsula and Scotia Sea in the austral summer of 2019-2020. Constrained correspondence analysis (CCA) and generalized additive models (GAM) were used to relate seabird community composition, density, and species richness to environmental covariates. Results: Species assemblages differed between oceanographic areas, with sea surface temperature and distance to coast being the most important predictors of seabird distribution. Our results further revealed a geographic separation of distinct communities rather than hotspot regions in the study area in summer. Discussion: These findings highlight the importance of large-scale environmental characteristics in shaping seabird community structure, presumably through underlying prey distribution and interspecific interactions. The present study contributes to the knowledge of seabird distribution and habitat use as well as the baseline for assessing the response of Antarctic seabird communities to climate warming. We argue that cruise vessels, when combined with structured research surveys, can provide a cost-effective additional tool for the monitoring of community and ecosystem level changes.
Keywords: Antarktis; Sørishavet; marin biologi; marin zoologi; marine økosystemer; sjøfugler

Xenobiotic metabolism and its physiological consequences in high-Antarctic Notothenioid fishes - Strobel, Anneli; Lille-Langøy, Roger; Segner, Helmut; Burkhardt-Holm, Patricia; Goksøyr, Anders; Karlsen, Odd André (Polar Biology, 2022)
The Antarctic ecosystem is progressively exposed to anthropogenic contaminants, such as polycyclic aromatic hydrocarbons (PAHs). So far, it is largely unknown if PAHs leave a mark in the physiology of high-Antarctic fish. We approached this issue via two avenues: first, we examined the functional response of the aryl hydrocarbon receptor (Ahr), which is a molecular initiating event of many toxic effects of PAHs in biota. Chionodraco hamatus and Trematomus loennbergii served as representatives for high-Antarctic Notothenioids, and Atlantic cod, Gadus morhua as non-polar reference species. We sequenced and cloned the Ahr ligand binding domain (LBD) of the Notothenioids and deployed a GAL4-based luciferase reporter gene assay expressing the Ahr LBD. Benzo[a]pyrene (BaP), beta-naphthoflavone and chrysene were used as ligands for the reporter gene assay. Second, we investigated the energetic costs of Ahr activation in isolated liver cells of the Notothenioids during acute, non-cytotoxic BaP exposure. In the reporter assay, the Ahr LBD of Atlantic cod and the Antarctic Notothenioids were activated by the ligands tested herein. In the in vitro assays with isolated liver cells of high-Antarctic Notothenioids, BaP exposure had no effect on overall respiration, but caused shifts in the respiration dedicated to protein synthesis. Thus, our study demonstrated that high-Antarctic fish possess a functional Ahr that can be ligand-activated in a concentration-dependent manner by environmental contaminants. This is associated with altered cost for cellular protein synthesis. Future studies have to show if the toxicant-induced activation of the Ahr pathway may lead to altered organism performance of Antarctic fish.
Keywords: Sørishavet; fisker; marin zoologi; marinbiologi

Pathogen surveillance in Southern Ocean pinnipeds - Núñez-Egido, Sandra; Lowther, Andrew; Nymo, Ingebjørg H.; Klein, Jörn; Breines, Eva M.; Tryland, Morten (Polar Research, 2020)
Knowledge of the health status and potential effect of disease outbreaks among Southern Ocean fauna may be decisive for its conservation. We assessed the exposure and infection of Antarctic fur seals (Arctocephalus gazella, AFS) and Southern elephant seals (Mirounga leonine, SES) to parapoxvirus, Phocid alphaherpesvirus-1 (PhHV-1), smooth Brucella spp. and Toxoplasma gondii. AFS (n = 65) serum and swab samples, and SES (n = 13) serum samples from the sub–Antarctic island of Bouvetøya (54°25’S, 03°22’E) were collected during two austral summers (2014/15, 2017/18). Three polymerase chain reaction (PCR) tests amplifying the DNA polymerase, B2L and GIF parapoxvirus genomic regions were performed, investigating DNA from mucosal swab samples. The glycoprotein B gene was targeted to detect PhHV-1 viral DNA. Sera were assayed for T. gondii and smooth Brucella spp. antibodies with indirect enzyme-linked immunosorbent assays. Parapoxvirus PCR amplicons of the expected size were generated in two of the 29 AFS pups (nasal swabs, 2014/15), targeting the B2L (n = 2) and DNA polymerase (n = 1) genes, whereas the GIF PCR did not amplify target sequences. The PCR amplicons were sequenced and blasted in GenBank, revealing highest similarity with a seal parapoxvirus, confirming the presence of the virus in AFS for the first time. No PhHV-1 amplicons were generated, and antibodies against T. gondii or smooth Brucella spp. were not detected. Our data indicate that these seals are host for parapoxvirus but are neither exposed to smooth Brucella spp. nor T. gondii. Evidence of PhHV-1 shedding was not detected.
Keywords: Bouvetøya; Sørishavet; epidemiologi; fylogenetikk; infeksjon; marin biologi; marin zoologi; pelsseler; pinnipedier; serologi; sjøelefanter; virologi

Ontogenetic changes in the feeding strategy of Lepidonotothen nudifrons (Pisces, Nototheniidae) off the South Shetland Islands and the Antarctic Peninsula - Blasina, Gabriela; Cazorla, Andrea Lopez; Antoni, Mariana Deli; Bruno, Daniel; Delpiani, Matías; Díaz de Astarloa, Juan Martín (Polar Research, 2017)
The diet and feeding strategy of Lepidonotothen nudifrons off the South Shetland Islands and the Antarctic Peninsula, as well as their variation in relation to ontogenetic stage (juvenile– adult) and sampling area, were determined by stomach contents analysis. Additionally, the trophic level of this species was estimated to determine its position within the Antarctic food web. Out of 247 specimens with prey in their stomachs, 144 were caught near the South Shetland Islands and 103 off the Antarctic Peninsula. Ontogenetic changes in the trophic ecology of L. nudifrons were observed in both areas and were mainly related to a decrease of copepods and an increase of euphausiids in the diet. The diet of juveniles from the South Shetland Islands was characterized by the dominance of calanoid copepods, followed by isopods and amphipods, whereas diet off the Antarctic Peninsula was dominated by amphipods and cyclopoid copepods. The diet in adults was dominated by amphipods and euphausiids in both areas. The specialization of individual predators on different prey types was observed when considering the whole population of L. nudifrons, but when ontogenetic stages were considered separately it showed a more mixed feeding strategy, with different dominant prey for each class. Although the trophic level increased with fish size, L. nudifrons can be classified as secondary consumer throughout its lifespan.
Keywords: Sørishavet; amfipoder; copepoder; euphausiacea; fauna; fisker; isopoder; marin zoologi; økosystemer

Scleractinian corals recorded in the Argentinean Antarctic expeditions between 2012 and 2014, with comments on Flabellum (Flabellum) areum Cairns, 1982 - Schejter, Laura; Bremec, Claudia S; Cairns, Stephen D (Polar Research, 2016)
In this contribution, we provide a list of the scleractinian corals recorded during the Argentinean Antarctic expeditions on board the oceanographic vessel Puerto Deseado (Argentina) in the austral summers in 2012, 2013 and 2014. The identified taxa consist of six solitary species (Flabellum impensum, F. flexuosum, F. areum, Caryophyllia antarctica, Paraconotrochus antarcticus and Javania antarctica), recorded from 19 sampling sites located off the Antarctic Peninsula and South Shetland and South Orkney islands. We also update the information of F. areum, previously known only from south-west Atlantic waters, extending its distribution range to Antarctic waters and its upper bathymetric range to 218 m. Keywords: cold-water corals; Antarctica; range extension; bathymetric range extension; Scleractinia.
Keywords: Sørishavet; ekspedisjoner; koraller; marin zoologi; oseanografi

Reliability of VHF telemetry data for measuring attendance patterns of marine predators: a comparison with time depth recorder data - Lowther, A D; Ahonen, H; Hofmeyr, G; Oosthuizen, W C; De Bruyn, P J N; Lydersen, C; Kovacs, K M (Marine Ecology Progress Series, 2015)
Very high frequency (VHF) radiotelemetry data has been used for over 30 yr to monitor the behavior patterns of otariid seals. These data have been used in a wide variety of ways, from characterizing the reproductive and foraging ecology of these species to inferring ecosystem changes based on variation in attendance patterns. Yet the accuracy of VHF data has never been appropriately evaluated. Our study compares VHF data collected on 16 lactating Antarctic fur seals to assess onshore attendance with concurrently collected time depth recorder (TDR) data used as the true measurement of time spent onshore. Within the retrieved datasets, 25% of the VHF data could not be interpreted with any reliability. Additionally, there were significant differences in the number and duration of attendance bouts between the 2 instrument types, with VHF data overestimating attendance bout duration by approximately 8.9 h on average. Importantly, the magnitude and direction of errors between VHF and TDR measurements were not systematic, suggesting that VHF data is an inappropriate method for collecting attendance data. Modelling the raw VHF data in a state-space framework elicited mean attendance durations that were indistinguishable from TDR-derived measurements, suggesting this approach may provide a means to re-examine historic VHF data. Moreover, given the evolution of electronic tags in terms of sophistication, miniaturization, longevity and decreasing cost over the last 30 yr, TDRs are a more appropriate means of collecting attendance data on centrally foraging marine mammals such as otariids.
Keywords: Bouvetøya; NARE ekspedisjoner; Sørishavet; marin zoologi; overvåking; pelsseler; pinnipedier; radio telemetri; økosystemer

First record of humpback anglerfish (Melanocetus johnsonii) (Melanocetidae) in Antarctic waters - Orlov, Alexei M.; Orlova, Svetlana Y.; Volkov, Alexander A.; Pelenev, Dmitry V. (Polar Research, 2015)
The first record of the humpback anglerfish (Melanocetus johnsonii) in Antarctic waters (Ross Sea) is documented. Species identification is confirmed by the structure of the escal bulb and analysis of the mitochondrial cytochrome oxidase subunit I (COI) gene. This record extends the known range of M. johnsonii by more than 1000 nm to the south. The taxonomic status of Melanocetus species in Antarctic waters is discussed. Keywords: Melanocetus sp.; new record; taxonomy; distribution; Ross Sea; Antarctic.
Keywords: Rosshavet; Sørishavet; fisker; genetisk analyse; marin zoologi; taksonomi; zoogeografi

Instrumentation and handling effects on Antarctic fur seals (Arctocephalus gazella) - Blanchet, Marie-Anne; Lydersen, Christian; Biuw, Martin; de Bruyn, P J Nico; Hofmeyr, Greg; Krafft, Bjørn A.; Kovacs, Kit M. (Polar Research, 2014)
The use of biologging instruments has greatly improved our understanding of the behaviour, physiology and ecology of free-ranging marine mammals. However, handling wild animals and attaching instruments to streamlined bodies can cause stress and potentially influence behaviour and swimming/diving energetics. The goals of this study, undertaken on Bouvetøya, were (1) to determine if the first trip to sea after instrumentation is representative of subsequent trips in lactating Antarctic fur seals, to explore potential handling effects and assess possible biases in having multiple short-duration deployments (inflating N, using a limited number of tags) and (2) to evaluate potential effects of two different instrument combinations (SMRU satellite data relay loggers and very high frequency radio transmitters versus Wildlife Computers time–depth recorders and very high frequency radio transmitters) on trip durations, dive parameters, female body condition and pup growth. Handling did not appear to have any effects on the parameters studied; data from the first and second trips did not differ significantly. This implies that multiple short-term deployments are unlikely to result in biased data in this species. Instrument type did have measurable effects; time-at-sea was greater and pup growth was lower for pairs in which mothers carried bulkier instruments. This suggests that instrument streamlining is important to avoid negative impacts and that bulkier equipment should be deployed on lactating females with caution and only for short periods. The study highlights that instrument effects should be taken into account when comparing data from experiments collected using different equipment packages. Keywords: Bioenergetics; biologging; instrument effects; SRDLs; TDRs; VHFs.
Keywords: Bouvetøya; NARE ekspedisjoner; analyser; bioenergetikk; biologging; marin zoologi; pelsseler

New at-sea records of pelagic seabirds in the South Atlantic Ocean and Antarctica - Orgeira, José Luis; Scioscia, Gabriela; Torres, Mónica Anilía; Dellabianca, Natalia Andrea (Polar Research, 2013)
During ship-based seabird surveys in the south Atlantic and Antarctica in the austral summers of 1994/95, 2009, 2010, 2011 and 2012, we documented at-sea distributions of Buller’s albatross (Thalassarche bulleri), Atlantic petrel (Pterodroma incerta), soft-plumaged petrel (Pterodroma mollis), Kerguelen petrel (Lugensa brevirostris) and great-winged petrel (Pterodroma macroptera). In some cases, sightings were considered as extralimital, but for other species updating their distributions in the literature seems warranted. Atlantic petrel, for example, has been regularly observed in the Drake Passage and north of the Antarctic Peninsula for about 30 years, but the distribution of this species has not been updated in the literature. The observations reported here will contribute to update the at-sea distributions of these species and to changes in their distributions. Keywords: Seabirds; Antarctica; South Atlantic Ocean; distribution.
Keywords: Antarktis; Sørishavet; marin zoologi; observasjoner; ornitologi; petreller; sjøfugler

Estimates of the Southern Ocean general circulation improved by animal-borne instruments - Roquet, Fabien; Wunsch, Carl; Forget, Gael; Heimbach, Patrick; Guinet, Christophe; Reverdin, Gilles; Charrassin, Jean-Benoit; Bailleul, Frederic; Costa, Daniel P; Huckstadt, Luis A; Goetz, Kimberly T; Kovacs, Kit M; et al. (Geophysical Research Letters, 2013)
Over the last decade, several hundred seals have been equipped with conductivity-temperature-depth sensors in the Southern Ocean for both biological and physical oceanographic studies. A calibrated collection of seal-derived hydrographic data is now available, consisting of more than 165,000 profiles. The value of these hydrographic data within the existing Southern Ocean observing system is demonstrated herein by conducting two state estimation experiments, differing only in the use or not of seal data to constrain the system. Including seal-derived data substantially modifies the estimated surface mixed-layer properties and circulation patterns within and south of the Antarctic Circumpolar Current. Agreement with independent satellite observations of sea ice concentration is improved, especially along the East Antarctic shelf. Instrumented animals efficiently reduce a critical observational gap, and their contribution to monitoring polar climate variability will continue to grow as data accuracy and spatial coverage increase.
Keywords: Sørishavet; havis; hydrografi; klimatologi; marin biologi; marin zoologi; oseanografi; polarområdene; satellite bilder; seler; sjøis

Feeding grounds of the eastern South Pacific humpback whale population include the South Orkney Islands - Dalla Rosa, Luciano; Félix, Fernando; Stevick, Peter T; Secchi, Eduardo R; Allen, Judith M; Chater, Kim; Martin, Anthony R; Basso, Manuela (Polar Research, 2012)
This paper reports on two photo-identified humpback whales (Megaptera novaeangliae) that were sighted in different years in the proximity of the South Orkney Islands, at the boundary between the Scotia and Weddell seas (60o54.5’S – 46o40.4’W and 60o42.6’S – 45o33’W). One of the whales had been previously sighted off Ecuador, a breeding ground for the eastern South Pacific population. The other whale was subsequently resighted in Bransfield Strait, off the western Antarctic Peninsula, a well-documented feeding ground for the same population. These matches give support to a hypothesis that the area south of the South Orkney Islands is occupied by whales from the eastern South Pacific breeding stock. Consequently, we propose 40oW as a new longitudinal boundary between the feeding grounds associated with the eastern South Pacific and western South Atlantic breeding stocks. Keywords: Humpback whale; photo-identification; breeding stocks; migration; South Orkney Islands; Southern Ocean
Keywords: Rosshavet; Sørishavet; knølhvaler; marin zoologi; migrasjon; oseanografi

New insights into southern ocean physical and biological processes revealed by instrumented elephant seals - Charrassin, Jean-Benoît; Roquet, Fabien; Park, Young-Hyang; Bailleul, Frédéric; Guinet, Christophe; Meredith, Michael; Nicholls, K; Thorpe, Sally; McDonald, Birgitte; Costa, Daniel; Tremblay, Yann; Goebel, Michael; et al. (Proceedings of Ocean Obs 09: Sustained ocean observations and information for society, Venice, Italy, European Space Agency, 2009)
In recent years, the international “Southern Elephant seals as Oceanographic Samplers” (SEaOS) project has deployed miniaturized conductivity-temperature-depth satellite-relayed data loggers (CTD-SRDL) on elephant seals 1) to study their winter foraging ecology in relation to oceanographic conditions, and 2) to collect hydrographic data from polar regions, which are otherwise sparsely sampled. We summarize here the main results that have been published in both science components since 2003/2004. Instrumented southern elephant seals visit different regions within the Southern Ocean (frontal zones, continental shelf, and/or ice covered areas) and forage in a variety of different water masses (e.g. Circumpolar Deep Water upwelling regions, High Salinity Shelf Water), depending on their geographic distribution. Adult females and juvenile males from Kerguelen Is. forage pelagically in frontal zones of the Southern Indian Ocean, while adult males forage benthically over the Kerguelen Plateau and the Antarctic Continental Shelf, with the two groups feeding at different trophic levels as shown by stable isotopes analysis. Oceanographic studies using the data collected from the seals have, to date, concentrated on circumpolar and regional studies of the Antarctic Circumpolar Current (ACC) circulation. The temperature and salinity profiles documented by elephant seals at high latitudes, including below sea ice, have permitted quasi-circumpolar mapping of the southernmost fronts of the ACC. By merging conventional data and the high temporal and spatial resolution data collected by seal-borne SRDLs, it has been possible to describe precisely 1) the large-scale features of the ACC in the South Atlantic and its variability; 2) the circulation pattern over the Kerguelen plateau, revealing that the poorly known Fawn Trough concentrates an important proportion of the ACC flow in that region. Seals that foraged in ice covered areas have made eulerian time series available that have allowed for the estimation of sea ice formation rates, a parameter that is otherwise difficult to obtain, while also providing a unique description of the wintertime ocean circulation over the central Weddell Sea continental shelf. Finally, we present the first data collected by a newly-developed fluorescence sensor that as been embedded in the regular CTD-SRDL and deployed on elephant seals at Kerguelen. The fluorometer data obtained have offered the first synoptic view of the 3 dimensional distribution of temperature, salinity and fluorescence over a vast sector of the Southern Indian Ocean, allowing us to describe both vertical and horizontal variations in chlorophyll. This paper will make a core contribution to the Plenary Sessions 2C, 3A and 4A, and will be relevant to 2A and 2B.
Keywords: Bouvetøya; Sørishavet; marin biologi; marin zoologi; oseanografi

Wintertime ocean conditions over the southern Weddell Sea continental shelf, Antarctica - Nicholls, Keith W; Boehme, Lars; Biuw, Martin; Fedak, Michael A (Geophysical Research Letters, 2008)
During the austral winter of 2007 a Weddell Seal tagged with a miniaturized conductivity-temperature-depth (CTD) instrument travelled over the central southern Weddell Sea continental shelf. The instrument yielded 750 CTD profiles, 250 of them to the sea floor. The data show a full depth flow of water onto the shelf via a sill at the shelf break (74°S 44°W). The warmth from the core of the flow was able to maintain the surface mixed layer above the freezing point, resulting in a band of reduced ice-production. An estimate of the on-shelf flux suggests that this flow accounts for most of the estimated 3 Sv of water draining from the southern Weddell Sea continental shelf.
Keywords: Sørishavet; Weddellhavet; kontinentalsokkel; marin zoologi; oseanografi; saltinnhold; seler; temperatur

To slags minkehval i Antarktis = Two kinds of minke whale in the Antarctic - Williamson, Gordon R (Norsk hvalfangst-tidende, 1961)
Keywords: Sørishavet; hvaler; marin zoologi; zoologi

Gjenfundne hvalmerker i den antarktiske fangstsesong 1959/60 = Whale marks recovered in the Antarctic whaling season 1959/60 - Brown, S G (Norsk hvalfangst-tidende, 1960)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Gjenfundne hvalmerker i sesongene 1955/56 og 1958/59 i Antarktis og i Syd-Afrika i 1958 og 1959 = Whale marks recovered in the Antarctic seasons 1955/56, 1958/59, and in South Africa 1958 and 1959 - Brown, S G (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Spermhvalens forekomst i Sydishavet og månens eventuelle innflytelse på forekomstene = Occurrence of the sperm whale in the Antarctic and the possible influence of the moon - Holm, John L; Jonsgård, Åge (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Nytt funn av sverd fra sverdfisk (Xiphias gladius) i blåhval (Balaenoptera musculus) i Sydishavet = New find of sword from swordfish (Xiphias gladius) in blue whale (Balaenoptera musculus in Antarctic - Jonsgård, Åge (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; fisker; hvaler; marin zoologi; zoologi

Hvalmerking utført av norske hvalbåter i Antarktis i sesongene 1956/57 og 1957/58 : whale marking carried out by Norwegian catchers in the Antarctic, seasons 1956/57 and 1957/58 - Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1959)
Keywords: Sørishavet; hvalfangst; marin zoologi

Gjenfunne hvalmerker i den antarktiske sesong 1957/58 = Whale marks recovered during the Antarctic whaling season 1957/58 - Brown, S G (Norsk hvalfangst-tidende, 1958)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; zoologi

Undersøkelser av knølhvalen (Megaptera nodosa) i Bellingshausenhavet = Studies on the humpback whale (Megaptera nodosa) in the Bellingshausen Sea - Symons, H W; Weston, R D (Norsk hvalfangst-tidende, 1958)
Keywords: Sørishavet; hvaler; marin zoologi; zoologi

Gjenfunne hvalmerker i Antarktis i sesongen 1956/57 = Whale marks recovered during the Antarctic whaling season 1956/57 - Brown, S G (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; zoologi

Er det ønskelig og forsvarlig å utvide sesongen for fangst av knøl i Sydishavet? = Is it desirable and justified to extend the open season for humpback whaling in the Antarctic? - Jonsgård, Åge; Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi; marinbiologi

Rapport om hvalmerking utført av norske hvalbåter i Antarktis i sesongen 1955/56 = Report on whale marking carried out by Norwegian catchers in the Antarctic season 1955/56 - Ruud, Johan T; Øynes, Per (Norsk hvalfangst-tidende, 1957)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Om størrelsen av den antarktiske finnhvalbestand sett i relasjon til størrelsen av fangsten = On the size of the stock of Antarctic fin whales relative to the size of the catch - Ash, C E (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Nylig gjenfunne hvalmerker = Whale marks recently discovered - Brown, S G (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hval; hvaler; marin zoologi

Foreløpige beregninger av den sydlige bestand av store bardehval = Preliminary estimates of the southern populations of the larger baleen whales - Mackintosh, N A; Brown, S G (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hval; hvalfangst; marin zoologi

Om størrelsen av den antarktiske finnhvalbestand sett i relasjon til størrelsen av fangsten = On the size of the stock of Antarctic fin whales relative to the size of the catch - Ottestad, Per (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hval; hvalfangst; marin zoologi

Vet vi noe om bestanden av finnhval i Sydishavet? = Do we know anything about the stocks of fin whales in the Antarctic? - Ruud, Johan T (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Om størrelsen på den antarktiske finnhvalbestand sett i relasjon til fangstens størrelse = On the size of the Antarctic fin whale stock relative to the size of the catch - Symons, H W; Mackintosh, N A; Brown, S G; Salvesen, H K (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Beregninger av den sydlige bestand av store bardehval = Estimates of the southern populations of the larger baleen whales - Vangstein, Einar (Norsk hvalfangst-tidende, 1956)
Keywords: Sørishavet; hvaler; marin zoologi

Nylig gjenfunne hvalmerker = Whale marks recently recovered - Mackintosh, N A (Norsk hvalfangst-tidende, 1955)
Keywords: Sørishavet; hvaler; marin zoologi

Finn- og blåhvalenes trekk i Antarktis = The movements of fin and blue whales in Antarctic waters - Brown, S G (Norsk hvalfangst-tidende, 1954)
Keywords: Sørishavet; hvaler; marin zoologi

Finnhval (Balaenoptera physalus) med 6 fostre = Fin whale (Balaenoptera physalus) with six foetuses - Jonsgård, Åge (Norsk hvalfangst-tidende, 1953)
Keywords: Sørishavet; hvaler; marin zoologi

Finnes det et fredningsfelt for bardehval i Antarktis? = Does there exist a sanctuary for baleen whales in the Antarctic? - Schubert, Kurt (Norsk hvalfangst-tidende, 1953)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

Nylig gjenfundne hvalmerker = Whale marks recently recovered (Norsk hvalfangst-tidende, 1952)
Keywords: Sørishavet; hvaler; marin zoologi

Undersøkelser over blåhvalens alder i de antarktiske pelagiske fangster 1945/46 - 1948/49 = Investigations of the age of the blue whales in the Antarctic pelagic catches 1945/46 - 1948/49 - Ruud, Johan T (Norsk hvalfangst-tidende, 1950)
Keywords: Sørishavet; hvaler; marin zoologi

Hvalrådets skrifter no.20: scientific results of marine biological reseqarch - Bergersen, Birger; Lie, J; Ruud, Johan T (Norsk hvalfangst-tidende, 1940)
Keywords: Sørishavet; forskning; hvaler; hvalfangst; marin zoologi

Experimental investigations on the respiratory function in diving mammals and birds - Scholander, P F (I kommisjon hos Dybwad, 1940)
Publication Title: Hvalrådets skrifter : scientific results of marine biological research
Keywords: Antarktis; marin biologi; marin zoologi; ornitologi; pingviner

Hvalmaalinger i Rosshavet (Norsk hvalfangst-tidende, 1928)
Keywords: Sørishavet; hvaler; hvalfangst; marin zoologi

A new Antarctic expedition - Darnley, Rowland (Norsk hvalfangst-tidende, 1923)
Keywords: Sørishavet; ekspedisjoner; hvaler; marin zoologi